The contextual awareness, response and evaluation (CARE) diabetes project: study design for a quantitative survey of diabetes prevalence and non-communicable disease risk in Ga Mashie, Accra, Ghana - Swaib Abubaker Lule; Sandra Boatemaa Kushitor; Carlos S. Grijalva-Eternod; Kafui Adjaye-Gbewonyo; Olutobi Adekunle Sanuade; Mawuli Komla Kushitor; Lydia Okoibhole; Raphael Awuah; Leonard Baatiema; Irene Akwo Kretchy; Daniel Arhinful; Ama de-Graft Aikins; et al. (Taylor & Francis Group, 2024)
Diabetes is estimated to affect between 3.3% and 8.3% of adults in Ghana, and prevalence is expected to rise. The lack of cost-effective diabetes prevention programmes designed specifically for the Ghanaian population warrants urgent attention. The Contextual Awareness, Response and Evaluation (CARE): Diabetes Project in Ghana is a mixed methods study that aims to understand diabetes in the Ga Mashie area of Accra, identify opportunities for community-based intervention and inform future diabetes prevention and control strategies. This paper presents the study design for the quantitative survey within the CARE project. This survey will take place in the densely populated Ga Mashie area of Accra, Ghana. A household survey will be conducted using simple random sampling to select households from 80 enumeration areas identified in the 2021 Ghana Population and Housing Census. Trained enumerators will interview and collect data from permanent residents aged ≥ 25 years. Pregnant women and those who have given birth in the last six months will be excluded. Data analysis will use a combination of descriptive and inferential statistics, and all analyses will account for the cluster sampling design. Analyses will describe the prevalence of diabetes, other morbidities, and associated risk factors and identify the relationship between diabetes and physical, social, and behavioural parameters. This survey will generate evidence on drivers and consequences of diabetes and facilitate efforts to prevent and control diabetes and other NCDs in urban Ghana, with relevance for other low-income communities.